A simulation study for the upgrading of biogas using aqueous ammonia - Abdeen, Fouad R. H.; Mel, Maizirwan; Jami, Mohammed Saedi; Ihsan, Sany Izan; Ismail, Ahmad Faris (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Biogas upgrading process is usually performed for the removal of impurity gases (mainly carbon dioxide) other than methane from the biogas mixture. Being operated at high pressure and low temperature, both physical and chemical conventional upgrading methods lack energy efficiency. While a high pressure is used in the most common physical process; the high pressurized water scrubbing method, the widely spread chemical method of amine scrubbing is operated at high temperature gradient between the absorption and regeneration steps. In the current study, biogas upgrading using aqueous ammonia is proposed to replace the other conventional methods. An improved process of aqueous ammonia scrubbing operated at ambient or near ambient temperature and pressure is discussed for the purpose of removing carbon dioxide from biogas. A flow diagram for the process was built using the Aspen Hysys software provided by Aspen Tech®. The simulation results have shown that the proposed process, due to the high purity methane produced and being operated at ambient temperature and pressure, has a high potential in replacing the conventional upgrading methods.